Penerapan Teknologi Eco-Effisiensi Dan Green Economy Dalam Upaya Menuju UKM Tahu Mandiri Energi Di Kelurahan Margoagung, Kepenawon Seyegan Kabupaten Sleman - Rahayu, Suparni Setyowati; Nansi, Maria Regina; Arbintarso, Ellyawan S (Universitas Islam Nahdlatul Ulama Jepara, 2022)
The Community Partnership Program at the Khale Tahu Sehat UKM in Margoagung Village, Kapanewon Seyegan, Sleman Regency aims to realize the role of IST AKPRIND Yogyakarta with the output of a superior research strategy plan on renewable energy and environmental engineering in a more real way in partner SMEs. One of the home industry clusters that has received a lot of attention from an environmental perspective is the small tofu industry located in the Margoagung Village. The rapid development of the small tofu industry will have a positive impact on progress that brings an increase in the economic income of rural communities. However, the waste generated from the tofu production process will have a negative impact on the village environment, becoming smelly and dirty. Based on these negative impacts, tofu waste water from small industries in rural areas has the potential to pollute the environment if it is disposed of directly without any treatment. Soil pollution can occur when wastewater seeps into the ground and can result in resident wells close to the seepage of the wastewater that cannot be used anymore. Therefore, it is necessary to develop technology for wastewater treatment that can produce biogas as renewable energy that can be developed so that it is beneficial for the community rural population (eco-efficiency technology). The use of this waste management method is not only